The Effects of Cognitively Guided Instruction with Inductive Learning Management on Mathematical Problem Solving and Reasoning Abilities of Mathayomsuksa 3 Students - Chancharoen, Saowalak; Treepiboon, Komsan; Jenjit, Apunchanit (Mahachula Academic Journal, 2024)
The purposes of this research were; (1) to compare mathematical problem solving ability of Mathayomsuksa III students after learning with CGI and inductive learning management with the criterion 70% and; (2) to compare mathematical reasoning ability of Mathayomsuksa III students after learning with CGI and inductive learning management with the criterion 70%. The sample were 37 students of Mathayomsuksa III students of the second semester in academic year B.E 2566 they were selected by cluster random sampling method. The research instruments used in this research consisted of; (1) five lesson plans on circle using CGI and inductive learning management, (2) Mathematical problem solving and reasoning abilities test, with the reliability of 0.81. The statistical for analyzing the collected data were mean, standard deviation and t-test for one sample. The result indicated that (1) Mathematical problem solving ability of Mathayomsuksa III students after learning with CGI and inductive learning management was higher than the set criterion of 70% at .05 level of statistical significance. (2) Mathematical reasoning ability of Mathayomsuksa III students after learning with CGI and inductive learning management was higher than the set criterion of 70% at .05 level of statistical significance.